Mobile Game-Based Learning Framework to Enhance Student Engagement in Islamic Higher Education - Achmad Faqihuddin; Abdillah Muflih (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2025)
This study aims to design and implement a Game-Based Learning (GBL) model to enhance student engagement in Islamic Education (PAI) at the higher education level. The main issue addressed is the low student engagement due to the dominance of lecture-based methods and distractions from smartphone use in class. Generation Z students, in the digital era, demand more interactive and contextual learning models. A game-based learning approach is an innovative solution, turning digital devices from distractions into engaging Islamic learning tools. This research adopts the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The analysis phase involved interviews with five Islamic Education lecturers, analyzed using NVivo 12 software to identify learning needs. The design phase produced a six-stage GBL flow: orientation, exploration, interaction, reflection, evaluation, and closure. The development phase used the Wayground platform, integrating features like Voting, Word Cloud, Quiz, and Essay Response for interactive learning. The model was tested on 100 PAI students to measure effectiveness. Findings show significant improvements in cognitive, affective, and behavioral engagement, making students more active, motivated, and reflective on Islamic values. The model proved valid and effective, transforming smartphones into productive tools for Islamic learning.